Structural and AC magnetic properties of (Ni0.4Cu0.15Zn0.45)1-xMnxFe2O4(x=0.30, 0.45) due to Mn substitution - Mridula, Zarrin Tasnim (BRAC Univeristy, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Applied Physics and Electronics, 2017.